Correlation of Liver Fibrosis using Noninvasive Transient Elastography with Histological Staging in Infants with Cholestasis - A Prospective Analytical Study - Deepti Naik; Santosh Kumar Mahalik; Mukund Namdev Sable; Amit Kumar Satpathy; Manas Kumar Panigrahi (Journal of Indian Association of Pediatric Surgeons)
Aims: This study primarily aimed to correlate liver fibrosis (LF) assessed by transient elastography (TE) using liver stiffness measurement (LSM score) with liver biopsy fibrosis scoring (METAVIR score) in biliary atresia (BA). Secondary objectives were to assess the diagnostic accuracy of TE in distinguishing BA from other causes of neonatal cholestasis (NC) and the correlation of preoperative LSM score with surgical outcomes 3 months post Kasai portoenterostomy. Methodology: Infants under 6 months with conjugated hyperbilirubinemia (July 2022–February 2024) were cases and age- and gender-matched healthy infants served as controls. Cases were evaluated using predefined standard diagnostic tests and TE using Fibroscan® Expert 630 (Echosens) device was additionally performed preoperatively and 3 months postoperatively. METAVIR scoring was calculated on liver histopathology. Results: Fifty-one NC patients (28 boys, 23 girls) were included. A preoperative LSM ≥ 11.4 predicted significant fibrosis (METAVIR score – F3/F4) with 94% sensitivity and 46% specificity (P = 0.053). A preoperative LSM ≥ 13.2 fairly predicted the presence of BA with 74% sensitivity, 71% specificity (P = 0.006), and 72.5% diagnostic accuracy. Median preoperative LSM (interquartile range) for clearance of jaundice (COJ) (14.1 [10.28–18.48]) versus no clearance (15.7 [12.1–35]) showed no statistical difference (P = 0.359). Discussion and Conclusion: TE is an effective noninvasive screening tool to differentiate BA from other causes of NC with a cutoff of >13.2 kPa. The predictive value of TE for postoperative COJ and complications like cholangitis based on the preoperative LF measurements cannot be commented on based on our results.